HPV-associated head and neck cancer is characterized by distinct profiles of CD8+ T cells and myeloid-derived suppressor cells - Kansy, Benjamin Alexander; Wehrs, Tim P.; Bruderek, Kirsten; Si, Yu; Ludwig, Sonja; Droege, Freya; Haßkamp, Pia; Henkel, Uta; Dominas, Nina Tatjana Maria; Hoffmann, Thomas K.; Horn, Peter A.; Schuler, Martin; et al. (Cancer immunology immunotherapy, 2023)
Patients with HPV−-localized head and neck cancer (HNC) show inferior outcomes after surgery and radiochemotherapy compared to HPV-associated cancers. The underlying mechanisms remain elusive, but differences in immune status and immune activity may be implicated. In this study, we analyzed immune profiles of CD8+ T cells and myeloid-derived suppressor cells (MDSC) in HPV+ versus HPV− disease.